Mobile application with business intelligence to optimize the control process of tourist agencies - Luis Angel Valenzuela Ygnacio; Margarita Giraldo Retuerto; Laberiano Andrade-Arenas (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Currently, tourism companies do not have a strict control of clients, drivers, buses, guides and tickets; Drivers are known to drive at excessive speed and put their lives and the lives of their customers at risk, this occurs because drivers want to gain more passengers or race with a car from the same company. For this reason, the research work aims to optimize the travel control process for tourism companies by applying business intelligence. The kimball methodology was used, which allows making a dimensional model with dimensions and a central table of the process or event that occurs in real time, tourism companies would be benefiting since in decision-making in the field of travel control, they would have the most relevant data. In addition, users are also beneficiaries, clients who minimize risks when acquiring the tourism service, this would increase more profits for the tourism company and increase its clientele.